FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMPSIA PADA IBU HAMIL DI RSU SUNDARI MEDAN - Siti Aisyah; Br Sembiring, Juliana; Sikumbang, Sri Rintani (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2022)
Pre-eclampsia is one of the causes of maternal mortality, around 830 women die from complications of pregnancy or childbirth worldwide every day, it is estimated that in 2015 around 303,000 women died after childbirth. Risk factors for pre-eclampsia are mothers with a history of diabetes mellitus, hypertension and obesity. This study aims to determine the factors associated with the incidence of preeclampsia at RSU Sundari Medan in 2021. The design of this study was an analytical survey with a cross sectional approach, the number of samples used was 79 respondents with the sampling technique using the total sampling method. Data obtained by secondary data were analyzed by Chi Square statistical test with p value (0.05). Based on the results of research conducted at RSU Sundari Medan in 2021 using the chi square statistical test, it shows that there is a relationship between obesity and the incidence of preeclampsia with a p-value of 0.004, there is a relationship between Diabetes Mellitus and the incidence of preeclampsia with a p-value of 0.002, there is a relationship between history Hypertension with the incidence of preeclampsia with a p-value of 0.010, it can be concluded that there is a relationship between obesity, diabetes mellitus, history of hypertension and the incidence of pre-eclampsia with a p-value of less than 0.05. Suggestions for health workers can provide education to prevent the occurrence of pre-eclampsia in pregnant women. The results of this study can also be used as a reference for implementing treatment and improving good health services in reducing the risk of preeclampsia in pregnant women and can be used as additional knowledge of pregnant women about the risk of preeclampsia.